Breeding of Ornidia obesa (Diptera: Syrphidae: Eristalinae) on Pig Carcasses in Brazil - Martins, E. [UNESP]; Neves, J. A. [UNESP]; Moretti, T. C. [UNESP]; Godoy, W. A. C.; Thyssen, P. J. [UNESP] (Entomological Soc Amer, 2010)
On Mho obesa F. (Diptera: Syrphidae) is usually neglected in forensic entomology, although adults are rather frequent on vertebrate carrion. In this study, conducted in southeastern Brazil in 2008, we used two pig carcasses, one killed by cocaine overdose and the other by shooting, to evaluate mainly the possible influences of the type of death on the larval development of O. obesa in the pig remains. We recorded the breeding of 218 adult specimens of this syrphid fly from the carcass killed by shooting, and none from the carcass killed by cocaine. These observations may open a new perspective for the use of O. obesa in forensic studies, considering its breeding preferences and its complete development on vertebrate carrion.
Keywords: flower fly; tribe Volucellini; vertebrate carcass; forensic entomology